Pretreatment of Corn Stover Using Supercritical CO2 with Water-Ethanol as Co-solvent - 吕惠生 任苗苗 张敏华 陈莹 (Chinese journal of chemical engineering, 2013)
Supercritical carbon dioxide,with water-ethanol as co-solvent,was applied to pretreat corn stover to enhance its enzymatic hydrolysis.The efficiency of pretreatment was evaluated by the final reducing sugar yield obtained from the enzymatic hydrolysis of cellulose.Under the operation conditions of pretreatment pressure 15 MPa,temperature 180 ℃ and time 1 h,the optimal sugar yield of 77.8℅ was obtained.Scanning electron microscopy（SEM） and chemical composition analysis were applied to the pretreated corn stover.The results showed that the surface morphology and microscopic structure of pretreated corn stover were greatly changed.After the pretreatment,the contents of hemicellulose and lignin were reduced obviously.Thus more cellulose was exposed,increasing the sugar yield.